ANALISIS EFEKTIVITAS TEKNIK TES DAN NON TES DALAM PENILAIAN PENDIDIKAN MODERN - Iqlil Khoerul Ma’mun; Dhini Maulidatul Isnaini; Ika Nur Iliza; Untung Arif Warasanto; Ma’mun Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Assessment plays a crucial role in determining the success of the learning process in modern education. The development of today's education system demands assessments that are not solely oriented toward academic outcomes but also capable of measuring students' attitudes and skills comprehensively. This study aims to analyze the application and effectiveness of test and non-test techniques in modern educational assessment. Test techniques are used to measure students' cognitive abilities through evaluation forms such as multiple-choice, essay, and other objective tests. Meanwhile, non-test techniques are utilized to assess affective and psychomotor aspects through observation, interviews, questionnaires, portfolios, and performance assessments. The method used in this study is a literature study by reviewing various scientific sources related to educational assessment. The results of the study indicate that test techniques are considered effective in measuring students' thinking skills and mastery of material, while non-test techniques are more effective in assessing the development of attitudes, character, and skills. The combination of these two techniques can produce an assessment system that is more comprehensive, objective, and in line with the needs of 21st-century education. Therefore, the balanced use of test and non-test techniques is essential to improve the quality of learning evaluation.